Current Role And Requirements Of Digital Pedagogy - Khurzoda Rakimova (Euro Asian Journal Publishing, 2024)
This article discusses the possibilities of digital methods used in pedagogy today in connection with the development of the digital economy. In particular, examples of digital methods were given: "I am on the screen", "See me, hear, understand", "I am in online communication", "My online story", "From word to picture, from picture to story".
Keywords: education; teaching; pedagogy; method